Plan or React? Analysis of Adaptation Costs and Benefits Using Integrated Assessment Models - Agrawala, Shardul (OECD Publishing, 2010)
Financing for adaptation is a core element in the ongoing international negotiations on climate change. This has motivated a number of recent global estimates of adaptation costs. While important from an agenda setting perspective, many of these estimates nevertheless have a number of limitations. They are typically static (i.e. estimated for one specific year), do not differentiate between investments in various types of adaptation or quantify the resulting benefits, and are delinked from policies and investments in greenhouse gas mitigation
Keywords: Environment